Infectious crystalline keratopathy: A case series - Mohan, Shalini; Sahai, Kunal; Gupta, Vinita (Nepalese Journal of Ophthalmology, 2022)
This is the case series of three patients of infectious crystalline keratopathy (ICK) presented to us after undergoing penetrating keratoplasty between 2010 to 2020. The lesions showed classical crystalline patterns and clinical diagnosis was made. The patients were treated by broad spectrum antibiotics till the complete resolution of the lesions. The cases highlight the clinical features, diagnosis and management of this rare and resistant disease.